Gene flow from an adaptively divergent source causes rescue through genetic and demographic factors in two wild populations of Trinidadian guppies. (4th February 2016) - Fitzpatrick, Sarah W.; Gerberich, Jill C.; Angeloni, Lisa M.; Bailey, Larissa L.; Broder, Emily D.; Torres‐Dowdall, Julian; Handelsman, Corey A.; López‐Sepulcre, Andrés; Reznick, David N.; Ghalambor, Cameron K.; Chris Funk, W.
Abstract: Genetic rescue, an increase in population growth owing to the infusion of new alleles, can aid the persistence of small populations. Its use as a management tool is limited by a lack of empirical data geared toward predicting effects of gene flow on local adaptation and demography. Experimental translocations provide an ideal opportunity to monitor the demographic consequences of gene flow. In this study we take advantage of two experimental introductions of Trinidadian guppies to test the effects of gene flow on downstream native populations. We individually marked guppies from the native populations to monitor population dynamics for 3 months before and 26 months after gene flow. We genotyped all individuals caught during the first 17 months at microsatellite loci to classify individuals by their genetic ancestry: native, immigrant, F1 hybrid, F2 hybrid, or backcross. Our study documents a combination of demographic and genetic rescue over multiple generations under fully natural conditions. Within both recipient populations, we found substantial and long‐term increases in population size that could be attributed to high survival and recruitment caused by immigration and gene flow from the introduction sites. Our results suggest that low levels of gene flow, even from a divergent ecotype, can provide a substantial demographic boost to small populations, which may allow them to withstand environmental stochasticity.